The Last Swiddens of Sarawak, Malaysia - Ole, Mertz; Kelvin, Egay; Thilde, Bech Bruun; Colding, Tina Svan (Springer US, 2013)
Swidden cultivation was observed to be under pressure but still persisting in many areas in Sarawak, Malaysia around 2000–2003. Since then rapid development of smallholder oil palm and rubber, continuing urbanization and rural to urban migration appear to have considerably reduced the area under swidden cultivation. With the aim of understanding the extent and impacts of this development, 55 households in three communities that were interviewed in 2002–2003 were re-interviewed in 2011. In an area with rapid oil palm development, the households engaged in smallholder oil palm production have experienced considerable improvements in income and wealth whereas the other households have experienced more limited wealth increases or even a decline in income. Many households have decreased or abandoned cultivation of upland rice, which used to be the core of the swidden cultivation system, and the upland soils in the area are now dominated by oil palm. In another area, where no oil palm development has taken place because of a hydroelectric dam, upland rice fields under swidden cultivation have also decreased and new high yielding rubber is now being planted because of the favorable rubber prices. Moreover, tourism has in this area gained further economic importance and overtaken agriculture as the main economic activity of households. The demise of swidden has not yet occurred in Sarawak, but a continued decline has been observed. However, there is a possibility that the new smallholder oil palm and rubber may provide an opportunity for a new type of ‘productive fallow’ that will allow continued cultivation of upland rice on a small scale.